Therapeutic Targeting of the Soluble Guanylate Cyclase - Makrynitsa, Garyfallia I; Zompra, Aikaterini A; Argyriou, Aikaterini I; Spyroulias, Georgios A; Topouzis, Stavros (Current medicinal chemistry, 2019)
The soluble guanylate cyclase (sGC) is the physiological sensor for nitric oxide and alterations of its function are actively implicated in a wide variety of pathophysiological conditions. Intense research efforts over the past 20 years have provided significant information on its regulation, culminating in the rational development of approved drugs or investigational lead molecules, which target and interact with sGC through novel mechanisms. However, there are numerous questions that remain unanswered. Ongoing investigations, with the critical aid of structural chemistry studies, try to further elucidate the enzyme's structural characteristics that define the association of "stimulators" or "activators" of sGC in the presence or absence of the heme moiety, respectively, as well as the precise conformational attributes that will allow the design of more innovative and effective drugs. This review relates the progress achieved, particularly in the past 10 years, in understanding the function of this enzyme, and focusses on a) the rationale and results of its therapeutic targeting in disease situations, depending on the state of enzyme (oxidized or not, heme-carrying or not) and b) the most recent structural studies, which should permit improved design of future therapeutic molecules that aim to directly upregulate the activity of sGC.